Scoping review of approaches used for remote‐access parathyroidectomy: A contemporary review of techniques, tools, pros and cons. Issue 8 (25th April 2022) - Saito, Yoshiyuki; Ikeda, Yoshifumi; Takami, Hiroshi; Abdelhamid Ahmed, Amr H.; Nakao, Atsushi; Katoh, Hiroshi; Ho, Keiso; Tomita, Masato; Sato, Michio; Tolley, Neil S.; Randolph, Gregory W.
Abstract: After our coauthors described the first remote‐access parathyroidectomy (RAP) series in 2000, several other approaches were developed. No systematic review has been performed to classify and evaluate RAP techniques. We performed a literature search using PubMed and Cochrane Library (CENTRAL). A total of 71 studies met our inclusion/exclusion criteria. RAP can be categorized into five approaches: (1) endoscopic and robotic axillary, (2) anterior chest, (3) transoral, (4) retroauricular, and (5) a combination of these approaches. The limited data in the literature suggest that the cure rates and safety of RAP are in no way inferior to those of open parathyroidectomy. Each approach has its advantages and disadvantages, and the recommendations for the selection of each approach are listed. The selection of approach methods might depend on the surgeon's experience and familiarity and the patient's preference and disease status.